Novel weight functions and stress intensity factors for quarterelliptical cracks in lug attachments (Fracture and Structural Integrity, 2018)
In this paper, a general weight function was developed to calculate the stress intensity factors (SIFs) for quarter-elliptical cracks in a wide range of lug attachment family. For this purpose, a series of finite element analyses were conducted to achieve this weight function. Finally, using this unique extracted weight function, the influence of the pin loading model and crack parameters (aspect ratio and relative depth of the quarter-elliptical crack) on the SIFs was evaluated in the cracked lug attachments. The results of the present work were compared with those in the literature, which are compatible with them in those cases.
Keywords: Attachment lug; quarter-elliptical crack; weight function; stress intensity factor; 3D finite element analysis